Evaluation of The Utility of TPACK-Based Interactive Flat Panel (IFP) in Improving The Digital Literacy Skills of Elementary School Teachers in The Cimurah Garut Group - Indriani Desira Irawati; Jamilah Jamilah; Ayu Puji Rahayu (Riviera Publishing, 2026)
This research aims to evaluate the use of Interactive Flat Panel (IFP) based on Technological Pedagogical Content Knowledge (TPACK) in improving the digital literacy skills of elementary school teachers in the Cimurah Cluster, Garut Regency. The study used a mixed method with a sequential explanatory design, namely the collection and analysis of quantitative data followed by in-depth qualitative data. The research subjects consisted of 45 elementary school teachers in the Cimurah Cluster, Garut. Data collection techniques were carried out through questionnaires, observations, in-depth interviews, and documentation. The results showed that the use of TPACK-based IFP had a positive influence on improving teachers' digital literacy, especially in aspects of mastery of learning technology, digital media creativity, digital communication, and the ability to integrate technology into learning. Quantitatively, there was an increase in teachers' digital literacy skills by 78% in the high category. Meanwhile, qualitative results showed that the use of IFP was able to improve the effectiveness of interactive learning and teacher motivation in developing digital learning innovations. The main obstacles found included limited technical training, unstable internet access, and differences in digital competencies between teachers. This study recommends strengthening TPACK training based on digital technology on an ongoing basis in elementary schools.